Liminal transformations: folding the surface of the photograph - Nour Dados (Conserveries Mémorielles)
At once a material object and a multitude of paths, the photograph is a useful place to begin thinking about the threshold. In the photograph we might dwell on the nuances of the threshold, its ability to be an ‘inbetween’ and a gateway to a ‘beyond’ simultaneously. Indeed, the photograph offers both possibilities. The work of Bhabha, Benjamin and Sontag elucidates this slippage. In this uncertainty, ‘inbetween’ and ‘beyond’ signal another productive intersection.  The liminality of the threshold marks this terrain as a spatial transgression that ushers in a temporal disjuncture. The threshold is a shadow zone, as ordinary as a stairwell and as transformative as a breakthrough. In attempting to map the threshold, the paper borrows from Deleuze and Marks on enfolding and unfolding as a means through which knowledge becomes accessible, or remains concealed. To some extent, mapping the threshold is a process that begins unfolding from the discussion of surface, gaze and perception. Yet despite these markers, mapping the threshold of photographs proves difficult and elusive. In this respect, Wittgenstein’s notion of ‘seeing aspects’ helps explain the way that the threshold always exceeds our attempts at mapping and defies perception. The paper examines this impasse through the ‘fold of the surface’, an action which transgresses the flatness of the image without altering it. Perhaps this is the closest we can be to the threshold without holding it.